2015
DOI: 10.4040/jkan.2015.45.3.439
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Korean Version of the HIV Self-Management Scale in Patients with HIV

Abstract: Purpose: The purpose of this study was to examine validity and reliability of Webel and colleagues' HIV Self-Management Scale when used with a Korean sample. Methods: The original 20-item HIV Self-Management Scale was translated into Korean using translation and back-translation. Nine HIV nurse experts tested content validity. Principal component analysis (PCA) and confirmatory factor analysis (CFA) of data from 203 patients was used to test construct validity. Concurrent validity was evaluated using correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
(16 reference statements)
3
16
4
Order By: Relevance
“…Higher scores indicated a higher level of self-management. This instrument can be seen as reliable since it achieved a Cronbach's α of .89 in Kim et al (2015) and one of .87 in the present study.…”
Section: Study Instrumentssupporting
confidence: 56%
See 1 more Smart Citation
“…Higher scores indicated a higher level of self-management. This instrument can be seen as reliable since it achieved a Cronbach's α of .89 in Kim et al (2015) and one of .87 in the present study.…”
Section: Study Instrumentssupporting
confidence: 56%
“…The health behavioral factor was measured with a self-management. This study used HIV Self-Management Scale (HSMS) by Webel et al (2012) that was tested on the Korean population by Kim et al (2015) for validity and reliability. This instrument was comprised of 20 questions in three categories that measured the self-management behavior of HIV-positive patients, and the sum of scores from each question ranged from 0-60 points.…”
Section: Study Instrumentsmentioning
confidence: 99%
“…Studies on HIV SM in high-income and upper-middle-income countries focus on three domains of SM, namely daily physical health practice, social support, and living with HIV [ 6 , 9 , 10 ]. Daily physical health practice refers to physical exercise, diet management, reducing stress, symptom management, managing drug side effects and implementing other recommended physical health activities.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study using the same scale and conducted in China indicated lower mean scores: daily physical health practice, 1.80 ± 0.42, activating social support, 1.47 ± 0.63, living with chronic HIV, 2.46 ± 0.43 and an overall mean SM score of 1.91 ± 0.36, which was interpreted as low [ 12 ]. A third study conducted in Korea using the same scale reported an overall SM mean score of 2.00 ± 0.49, again interpreted as low [ 9 ]. These findings demonstrate variable levels of SM across different international settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation